Solidarity in Europe: Citizens' Responses in Times of Crisis - Christian Lahusen, Maria T. Grasso, Christian Lahusen, Maria T. Grasso (Springer International Publishing, 2018)
This open access volume provides evidence-based knowledge on European solidarity and citizen responses in times of crisis. Does the crisis of European integration translate into a crisis of European solidarity, and if yes, what are the manifestations at the level of individual citizens? How strongly is solidarity rooted at the individual level, both in terms of attitudes and practices? And which driving factors and mechanisms contribute to the reproduction and/or corrosion of solidarity in times of crisis? Using findings from the EU Horizon 2020 funded research project "European paths to transnational solidarity at times of crisis: Conditions, forms, role-models and policy responses" (TransSOL), the books addresses these questions and provides cross-national comparisons of eight European countries – Denmark, France, Germany, Greece, Italy, Poland, Switzerland, and the UK. It will appeal to students, scholars and policymakers interested in the Eurocrisis, politics and sociology.